Physical Exercise Does Not Improve Colon Inflammation in Mice Induced Lambda Carrageenan - Qonitatillah, Ana; Wigati, Kristanti Wanito; Irawan, Roedi (Universitas Airlangga, 2020)
Inflammatory Bowel Disease (IBD) is a well known reported gastrointestinal tract disease, which the prevalence continous to increase in Southeast Asia and other developing countries. Animal model have already been widely used for gut inflammation study. Lambda (Î») carrageenan is a chemical substance which commonly used to induced inflammation in IBD animal models. Physical exercise is a non-pharmacological therapy recommended for IBD. However, further study is needed to determine the effects of this therapy. This study was aimed to determine the physical exercise effect on colon inflammation in mice induced Î»-carrageenan. Thirty-eight mice were divided into 2 groups. Control group (C) which induced with Î»-carrageenan and treatment group (T) which induced by Î»-carrageenan and treadmill exercise. The degree of colon inflammation was obtained by histopathological examination using Hematoxylin-Eosin (HE) staining and inflammation scoring system, which include inflammatory cell infiltration and intestinal architecture. All mice colon samples in both group were inflamed with varying degrees. The treatment group had a higher Inflammatory degree score than control group (p <0.05). Physical exercise does not improved the degree of colon inflammation in mice induced Î»-carrageenan due to uncontrolled stress induction and water intake containing Î»-carrageenan.